Multiband Antenna for RF Energy Harvesting - Nguyen, Ngan; Tuan, Ninh Nguyen; Nguyen, Quoc Cuong; Truong, Vu Bang Giang; Krairiksh, Monai; Le, Minh Thuy (My University, 2018)
This paper presents a multi resonant bow-tie slot antenna for Rectifying Antenna in Ambient RF Energy Harvesting (RFEH). The proposed antenna operates at five frequencies 0.9 GHz, 1.8 GHz, 2.1 GHz, 2.45 GHz and 5.8 GHz corresponding with ambient RF sources in our environment bychanging the position and size of the air gap on the traditional bow-tie antenna as well as bow-tie antenna. A good agreement is observed between the simulation and measurement results. The proposedantenna is suitable for high efficiency RF energy harvesting system.
Keywords: Co-planar strip lines; GSM; LTE; Rectifying antenna; RF energy harvesting; Slotted bow-tie antennas